Amount and speciation of N leached from a sandy soil fertilized with urea, liquid digestate, struvite and NH4‐enriched chabazite zeolite‐tuff. (23rd November 2022) - Ferretti, Giacomo; Galamini, Giulio; Medoro, Valeria; Faccini, Barbara
Abstract: The large use and the bad management of fertilizers that are applied to soil for improving crop production have dramatically impaired soil, water, and air quality. To meet the requirements to reduce nitrogen (N) losses and all the related negative impacts on the environment and food production, it is mandatory to substitute or at least partially substitute the use of inefficient and unsustainable fertilizers with more efficient alternatives. The aim of this paper was to address the amount and speciation of the N released by a sandy soil fertilized with "slow‐release fertilizers" and traditional fertilizers (urea and liquid digestate) by means of a series of column leaching experiments. The slow‐release alternatives were represented by NH4 ‐enriched zeolitic tuff and struvite, both obtained by recovering the N from liquid digestate. The treatments consisted of sandy soil fertilized with (i) urea (U) (ii) liquid digestate (LD), (iii) NH4 ‐enriched zeolitic tuff (N‐CHA) and (iv) struvite (STRV). Eight different flushing events were performed over 38 days, leachates were collected and analysed for total Kjeldahl N, organic‐N, NH4 + ‐N, NO3 − ‐N, NO2 − ‐N and pH. U and LD lost the majority of N within the first 2 flushing events as organic N and NH4 + ‐N, respectively. On the other hand, STRV and N‐CHA lost less N over the whole course of the experiment and with more balanced speciation. The mass balance outlined that after the experiment, native soil N was mined in U and LD treatments while in N‐CHA and STRV a fraction of N from the fertilizers was still present. The results showed a slow release of N which can be used more efficiently in agricultural applications, minimizing the N losses.